Seroprevalence of immunoglobulin M and G antibodies against SARS-CoV-2 in China - Xu, Xin; Sun, Jian; Nie, Sheng; Li, Huiyuan; Kong, Yaozhong; Liang, Min; Hou, Jinlin; Huang, Xianzhong; Li, Dongfeng; Ma, Tean; Peng, Jiaqing; Gao, Shikui; et al. (Nature medicine, 2020)
Detection of asymptomatic or subclinical novel human coronavirus SARS-CoV-2 infection is critical for understanding the overall prevalence and infection potential of COVID-19. To estimate the cumulative prevalence of SARS-CoV-2 infection in China, we evaluated the host serologic response, measured by the levels of immunoglobulins M and G in 17,368 individuals, in the city of Wuhan, the epicenter of the COVID-19 pandemic in China, and geographic regions in the country, during the period from 9 March 2020 to 10 April 2020. In our cohorts, the seropositivity in Wuhan varied between 3.2% and 3.8% in different subcohorts. Seroposivity progressively decreased in other cities as the distance to the epicenter increased. Patients who visited a hospital for maintenance hemodialysis and healthcare workers also had a higher seroprevalence of 3.3% (51 of 1,542, 2.5–4.3%, 95% confidence interval (CI)) and 1.8% (81 of 4,384, 1.5–2.3%, 95% CI), respectively. More studies are needed to determine whether these results are generalizable to other populations and geographic locations, as well as to determine at what rate seroprevalence is increasing with the progress of the COVID-19 pandemic. Serologic surveillance has the potential to provide a more faithful cumulative viral attack rate for the first season of this novel SARS-CoV-2 infection. Initial results of serological surveillance in China provide valuable data for estimation of the cumulative prevalence of SARS-CoV-2 infection in the general population.